3D Microprinting of Iron Platinum Nanoparticle‐Based Magnetic Mobile Microrobots. (22nd January 2021) - Giltinan, Joshua; Sridhar, Varun; Bozuyuk, Ugur; Sheehan, Devin; Sitti, Metin
Abstract : Magnetic Microrobots In article number 2000204, Metin Sitti and co‐workers demonstrate a 3D microprinted helical structure with embedded iron platinum (FePt) nanoparticles. These biocompatible helical microswimmers can swim over five body lengths per second, making them the fastest helical swimmer in the tens of micrometer scale.